The Ethics of Screening and Treating Persons with Hepatitis C: A Canadian Perspective - Apau Bediako, Ramseyer (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
In this article, I argue that the Canadian government’s position against screening for hepatitis C virus (HCV) and publicly funding HCV treatment is ethically unjustifiable. Cost of medication and likelihood of widening existing health inequality are the government’s argument for not funding HCV treatment and for also not having a screening program. I object to this position and argue in favour of a screening program and public funding of HCV treatment. I argue that these barriers are ethically unjust. Conclusively, being denied screening and early treatment is to be denied the best possible outcome.